COMPETITIVENESS OF MICRO AND SMALL COMPANIES IN THE PRESENCE OF FREE TRADE AGREEMENT (NAFTA) - Choy Zevallos, Elsa Esther (2010)
The participation of Micro and Small Peruvians companies (MYPES), to the recent trade liberalization, particularly the Free Trade Agreement (NAFTA), is almost nil, because it is firms that are not competitive and they face many obstacles to its development such as problems of access to markets, technological barriers and difficulties in obtaining credit facilities from the financial sector. Faced with the challenges of an Open Economy and Global, the Free Trade Agreement (NAFTA) represent a commercial opportunity for countries like Peru, as it depends on other countries to achieve growth of foreign trade. Trade liberalization and specifically the Free Trade Agreement, principally the United States, is a very good opportunity for Peruvian companies that are prepared and a great threat, for which they are not, requiring just competitiveness, as well said the former executive director of USAID MYPE Competitive, Juan Carlos Mathews, referring to the great challenge of the Peruvian Mypes front of the new economic landscape. The issue has as objective to point out what is the status of MYPES and the possibility of participation to the free trade agreement. It is a study and analysis of information related to micro and small domestic firms in different economic sectors. The competitiveness issue is of great interest in our country, especially as it relates to the MYPES against NAFTA, it represents a great challenge for these companies.